Simultaneous Bilateral Anterior Shoulder Fracture Dislocation Following a Seizure: A Case Report and Review of Literature - Alrushaydan, Ayman; Alsayed, Mokhtar; Alnefaie, Amer (International Journal of Innovative Research in Medical Science, 2023)
Simultaneous, Bilateral anterior fracture-dislocation of the shoulders is very rare complication of generalized seizures. most cases attributable to major trauma. Seizures and electric shock are a common cause of fractures and dislocations of shoulder although these are most commonly posterior injuries. We present interesting case report of diagnosis and treatment of a patient with bilateral anterior shoulder fracture dislocations following a seizure.